'Dear Hindu Friends': official Diwali greetings as a medium for diplomatic dialogue. Issue 3 (2nd July 2020) - Barbato, Melanie
ABSTRACT: This article discusses greeting messages as a genre of interreligious communication. Greeting messages are defined as official communication issued by religious institutions and addressed to the members of another religious community on the occasion of specific feast days or anniversaries. Drawing on the insights of politolinguistic analysis, this article treats these messages primarily as a form of public diplomacy. The case study analyses the messages issued on the occasion of the Hindu festival Diwali/Deepavali by the Pontifical Council for Interreligious Dialogue and World Council of Churches between 2015 and 2017. Distributed through the social media and posted on the institutional websites, the Diwali messages seek to speak as a Christian voice to all Hindus. Beyond the official addressee, the messages also potentially face the scrutiny of the global public sphere, especially an internal Christian readership. This article analyses what language strategies are used to deal with these varied demands.